Handbook of social media management : value chain and business models in changing media markets - Muhl-Benninghaus, Wolfgang; Friedrichsen, Mike (Media Business and Innovation, 2013)
Digitization and Web 2.0 have brought about continuous change from traditional media management to new strategic, operative and normative management options. Social media management is on the agenda of every media company, and requires a new set of specialized expertise on digital products and communication. At the same time, social media has become a vibrant field of research for media economists and media management researchers. In this handbook, international experts present a comprehensive account of the latest developments in social media research and management, consistently linking classical media management with social media. The articles discuss new theoretical approaches as well as empirical findings and applications, yielding an interesting overview of interdisciplinary and international approaches. The book's main sections address forms and content of social media; impact and users; management with social media; and a new value chain with social media. The book will serve as a valuable reference work for researchers, students and professionals working in media and public relations.